Barriers to and facilitators of point-of-care ultrasound utilization among physicians, nurse practitioners, and nurses in Japan: a comparative study - Toru Yamada; Takuma Kimura; Kyoko Shigetomi; Takahiro Shinohara; Shuji Ouchi; Suguru Mabuchi; Tomoko Kusama; Takeshi Ishida; Masayoshi Hashimoto (The Ultrasound Journal)
Abstract Background Point-of-care ultrasound (POCUS) is a valuable skill for generalist physicians, nurse practitioners (NPs), and nurses; however, its utilization remains limited. This study was performed to investigate the current status, barriers, and facilitators of POCUS implementation among physicians, NPs, and nurses in family and hospital medicine in Japan and to identify differences in influencing factors between physicians and NPs/nurses. Results A web-based survey was distributed via the mailing lists of four major academic societies in general medicine in Japan—the Japanese Society of Hospital General Medicine, the Japan Primary Care Association, the Japanese Association for Home Care Medicine, and the Japan Society of Nurse Practitioner—from April to June 2024. The respondents included physicians, NPs, and nurses affiliated with these societies. Responses from other professions, duplicate entries, and incomplete surveys were excluded from the analysis, resulting in 913 valid responses (692 physicians and 221 NPs/nurses). Physicians reported a higher POCUS implementation rate than NPs/nurses (73.0 vs. 63.4%, p = 0.006). The top two barriers were consistent across both groups: lack of training opportunities (p = 0.385) and lack of image acquisition skills (p = 0.369). However, NPs/nurses reported significantly greater barriers than did physicians, including lack of mentors (p < 0.001), lack of interpretation skills (p = 0.007), lack of confidence (p < 0.001), poor access to ultrasound devices (p < 0.001), and absence of institutional guidelines (p < 0.001). The top facilitators for both groups were good access to ultrasound devices (p = 0.078) and increased training opportunities (p = 0.240), with no significant differences between them. Compared with physicians, NPs/nurses expressed a significantly higher demand for nearby mentors (p < 0.001), institutional support (p < 0.001), and POCUS certification (p = 0.005). Conclusions There is currently a lack of POCUS training opportunities across all professional roles. To promote POCUS adoption among NPs and nurses, it is essential to develop mentorship programs, establish institutional guidelines, and create an environment that enables NPs and nurses to perform POCUS confidently through measures such as certification programs.